Method for predicting reaction activity of geopolymer precursor material

By mixing the geopolymer precursor material with NaOH solution and heating and stirring, the ion concentration and dissolution rate are determined, and the calculation model is established, which solves the problem of time-consuming and error in the prediction of the reaction activity of the geopolymer precursor material. It achieves rapid and accurate activity prediction, is suitable for the activity evaluation of composite materials, and improves the preparation efficiency of high-performance geopolymers.

CN119230010AInactive Publication Date: 2024-12-31CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202411759729.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the reaction activity prediction of the geopolymer precursor materials is time-consuming and labor-intensive, and the test environment and the actual application environment are different, resulting in large errors and the activity index of the composite material cannot be effectively evaluated.

Method used

By mixing the geopolymer precursor material with NaOH solution and heating and stirring, the ion concentration and solubility in the filtrate are measured after suction filtration, the activity index is tested by combining the intensity ratio method, and a calculation model for predicting the activity index is established to quickly predict the geopolymer precursor. reactivity of bulk materials.

Benefits of technology

It achieves rapid and accurate prediction of the reactive activity of geopolymer precursor materials, is suitable for different environments, can evaluate the activity index of composite materials, and improves the selection efficiency of high-performance geopolymers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230010A_ABST
    Figure CN119230010A_ABST
Patent Text Reader

Abstract

The invention provides a method for predicting reaction activity of a geopolymer precursor material, which comprises the following steps: S1, weighing the geopolymer precursor material A, and mixing with a NaOH solution; s2, heating and stirring the mixed solution in the S1, and reacting to obtain a composite solution; s3, carrying out suction filtration on the composite solution; drying and weighing filter residues obtained by suction filtration; s4, measuring the ion concentration in the filtrate obtained by suction filtration in S3; s5, calculating the dissolution rate of the A by using the mass of the A and the mass of the filter residues; s6, testing the actual activity index of the geopolymer precursor material A; s7, obtaining a calculation formula of the predicted activity index of A by using the dissolution rate and the ion concentration; and S8, solving a calculation formula of the actual activity index in S6 and the predicted activity index in S7 to obtain a calculation model of the predicted activity index of A. The problems that in the prior art, geopolymer precursor material reaction activity prediction is time-consuming and labor-consuming, not suitable for all environments and large in error are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material science and engineering, and particularly relates to a method for predicting the reaction activity of geopolymer precursor materials. Background Art

[0002] The prediction of the reaction activity of geopolymer precursor materials is of great significance for the preparation of high-performance geopolymers. Currently, there are many types of geopolymer precursor materials with complex compositions, and the reaction activity is difficult to predict. The traditional test of the activity index of the precursor material requires 28 days or 7 days of curing. The test based on the strength ratio method is time-consuming and labor-intensive, and has a long duration and low efficiency. The traditional method is to prepare the slurry through a single material + cement + water, which can only evaluate the reaction activity of a single material one by one, and cannot directly reflect the performance of the geopolymer material in actual application. At the same time, in the traditional test method, due to the large difference between the test environment and the actual reaction environment of the geopolymer material, that is, the alkaline environment, the test results have large errors. Therefore, there is an urgent need for a simple and effective method for predicting the reactivity of geopolymer precursor materials to solve the problem of difficulty in predicting reactivity due to the complex composition of geopolymer materials. Summary of the invention

[0003] The purpose of the present invention is to provide a method for predicting the reactivity of geopolymer precursor materials, so as to solve the problems in the prior art that the prediction of the reactivity of geopolymer precursor materials is time-consuming and labor-intensive, not applicable to all environments, and has large errors.

[0004] The technical solution adopted by the present invention is: A method for predicting the reactivity of a geopolymer precursor material comprises the following steps: S1: weighing geopolymer precursor material A with different ratios, mixing with NaOH solution and sealing; S2: placing the mixed solution of S1 in a heating device, heating and stirring, and obtaining a composite solution after the reaction is completed; S3: filtering the composite solution; drying and weighing the filter residue obtained by the filtration; S4: Determine the ion concentration in the filtrate obtained by filtration in S3; S5: Calculate the dissolution rate of A using the mass of geopolymer precursor material A in S1 and the mass of filter residue in S3; S6: testing the actual activity index of the geopolymer precursor material A of S1; S7: A calculation formula for obtaining a predicted activity index of geopolymer precursor material A using the dissolution rate of S5 and the ion concentration of S4; S8: Solve the calculation formula of the actual activity index of S6 and the predicted activity index of S7 to obtain a calculation model of the predicted activity index of the precursor material A.

[0005] Furthermore, in said S1, The mass of geopolymer precursor material A is M0; the concentration of NaOH solution is 1-3 mol / L; the mass ratio of geopolymer precursor material A to NaOH solution is 1:30-1:40.

[0006] Furthermore, in S2, The temperature is: 40~65℃; the stirring speed is: 800~2000 r / min; the stirring time is: 40~60min.

[0007] Further, the S3 includes: The composite solution is filtered using a vacuum filtration device, and the filtered filtrate is stored at a standard curing temperature; The solid residue obtained by filtration is washed, dried and weighed, and the mass is M1.

[0008] Further, the S4 includes: The Si, Al and Ca ion concentrations in the filtrate were determined within 24 h.

[0009] Further, the S5 includes: The dissolution rate of A The calculation formula is: .

[0010] Further, the S6 includes: The actual activity index of precursor material A was tested using the intensity ratio method. Precursor material A was mixed with cement to prepare concrete, and its 28-day strength was tested At the same time, pure cement was used to prepare concrete and its 28d strength was tested. , the actual activity index GAI of precursor material A is calculated as follows: .

[0011] Further, the S7 includes: Calculate the silicon activation index of precursor material A SAI and aluminum activation index AAI , the calculation formula is: ; in, is the Si ion concentration, is the Ca ion concentration, is the Al ion concentration, is the dissolution rate of precursor material A; Calculate the predicted activity index of precursor material A , the calculation formula is: ; in, and The values ​​are equal, is the activity contribution coefficient of silicon activation index, is the activity contribution coefficient of aluminum activation index.

[0012] Further, the S8 includes: According to S6 、 S7 Calculation formula, obtained through planning solution , , obtain the computational model for the predicted activity index of precursor material A.

[0013] The beneficial effects of the present invention are 1. The traditional method of testing the activity index of the precursor material requires 28 days or 7 days of curing and is tested according to the strength ratio method, which takes a long time and is inefficient. The reaction activity prediction method proposed in the present invention establishes a functional relationship with the activity index based on the ion concentration ratio and the dissolution rate, so as to achieve the purpose of quickly predicting the reaction activity of the geopolymer precursor material, and has the advantages of being fast and convenient.

[0014] 2. The traditional method is to prepare slurry by single material + cement + water to test the concrete strength. Since the test environment is quite different from the reaction environment of the actual geopolymer material, the error of the test result is relatively large. The method of the present invention is to obtain the ion concentration and dissolution rate of the precursor material in the alkaline solution, which is more in line with the alkaline environment in the geopolymer alkali excitation reaction.

[0015] 3. There are many kinds of geopolymer precursor materials, which can be used in combination. Different mass ratios lead to different activity indexes. Traditional methods can only evaluate the reaction activity of single materials one by one, and cannot directly reflect the performance of geopolymer materials in practical applications. The present invention can predict the activity index of any one or more precursor materials in any ratio through the precursor material activity index prediction model, providing a basis for selecting precursor materials for preparing high-performance geopolymers.

[0016] 4. The present invention can calculate the activity index according to the dissolution characteristics and determine the optimal proportion of the precursor material according to the activity index, which is faster than the traditional test method. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 Activity index of precursor material obtained by the method of the present invention and traditional method and accuracy graph of the method of the present invention. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] S1: Weigh 3 parts of geopolymer precursor material A, with a mass of M0, where A is a single or multiple geopolymer precursor materials prepared in a certain ratio, and mix them evenly with 100 parts of 1-3 mol / L NaOH solution; the ratio of geopolymer precursor material A to NaOH solution is 1:30-1:40 to ensure full dissolution; if the concentration of NaOH is too high, it will react with CaO in the precursor material to generate Ca(OH)2, and the solubility of Ca(OH)2 is low, which affects the subsequent Ca 2+ Concentration test: too low concentration will lead to incomplete dissolution of silicon oxide, aluminum oxide and calcium oxide, affecting the results; seal the mixed solution in a 250mL conical flask; S2: After the constant temperature water bath is raised to 40-65°C, heating is mainly to accelerate dissolution. If the heating temperature is too low, the dissolution will not be complete. The sealed conical flask is placed in the constant temperature water bath, and the mixture is continuously stirred at a speed of 800-2000 r / min with a magnetic stirrer for 40-60 minutes. If the time is too short, the dissolution will not be complete. The composite solution A is obtained. S3: Use a vacuum filtration device (pore size of 0.25 microns) to filter the composite solution A, bottle the filtrate after filtration in a test tube and store it in a refrigerated environment at 20±2°C (standard curing temperature); wash the solid residue obtained by filtration with clean water, then wash it with deionized water and ethanol three times respectively, and then vacuum dry it at 60°C for 24 hours, wash the residue with deionized water until the pH of the washing liquid is 7, and obtain residual solids. Put the residual solids into a vacuum dryer and dry them to constant weight to obtain substance B, which is weighed and recorded as M1; S4: The filtrate obtained after S3 filtration is placed in an inductively coupled plasma emission spectrometer to determine the dissolution amount of each element. In order to avoid errors, the element concentration test must be completed uniformly within 24 hours. Long-term storage will cause water loss in the solution. Since the main participants in the geopolymerization reaction are SiO2, Al2O3 and CaO, and the geopolymer hydration products are mainly composed of hydrated sodium silicate NASH and hydrated calcium silicate CASH, the instrument mainly detects the concentration of Si, Al, and Ca ions to obtain the three ion concentrations of precursor materials A with different compositions; S5: Calculate the ratio of the mass M1 of substance B to the mass M0 of the geopolymer precursor material weighed in the first step to obtain the dissolution rate P of the precursor material A with different compositions. Insoluble substances cannot participate in the geopolymerization reaction and can only act as fine aggregates, which are wrapped by the generated hydration products to form strength. Too low a dissolution rate is not conducive to the formation of cementitious products. The calculation formula of the dissolution rate P is as follows: ; Without considering the influence of alkaline activators, the dissolution rate of the precursor material and the concentration of Si, Al, and Ca ions precipitated are the main factors determining the strength of the geopolymer, and the strength is determined by the activity index.

[0021] S6: The activity index of the precursor material was tested using the strength ratio method. The content of precursor material A was 30% and the content of cement was 70%. Concrete was prepared and its 28-day strength was tested. ; Another pure cement concrete was prepared and its strength was tested after curing for 28 days , the activity index GAI of precursor material A is calculated as follows: ; S7: Using the dissolution rate of precursor material A with different compositions and the precipitation concentrations of Si, Al, and Ca ions, the SAI silicon activation index and AAI aluminum activation index are calculated, and the functional relationship between the geopolymer precursor material activity prediction index GAI' and SAI and AAI is established.

[0022] ; in: To predict the activity index for the precursor material, let and The values ​​are equal, is the activity contribution coefficient of silicon activation index, is the activity contribution coefficient of aluminum activation index, is the Si ion concentration, is the Ca ion concentration, is the Al ion concentration; According to the formation principle of geopolymers, the reason why SAI and AAI establish the following relationship is: first, Si / (Al + Ca), when the Ca content is very low, Si / Al has a great influence on the strength of geopolymers. When there is no calcium, the gel formed is NASH sodium aluminum silicate hydrate gel, when the calcium content is normal, the gel formed is NASH and calcium aluminum silicate hydrate CASH coexist, when the calcium content is sufficient, the gel formed is CASH and part of Ca (OH) 2, so SAI is used to evaluate the ratio of Si / (Al + Ca), and at the same time, the dissolution rate and the undissolved rate are used to balance the value of Si / Al + Ca to prevent the situation where the concentrations of Si, Al, and Ca are all very low and the ratio is very large; AAI is used to evaluate the proportion of Al. Regardless of the calcium content, Si and Al are necessary materials for forming gels, and the dissolution rate is also used to balance this value.

[0023] S8: The plurality of precursor materials A obtained according to S6 , corresponding to each precursor material A in S7 Calculation formula, obtained through planning solution , , and then the GAI prediction model of precursor material A was determined.

[0024] Using methods S1-S7, the experimental data in Table 1 were obtained; Table 1 shows the ion concentration, dissolution rate, SAI, AAI, activity index and precision of single or multiple precursor materials with different proportions composed of circulating fluidized bed fly ash CFBFA, blast furnace slag GGBS and waste concrete powder WCP.

[0025] Table 1 Parameters of single or multiple precursor materials with different ratios composed of CFBFA, GGBS, and WCP ; Constructing a relation , establish the following relationship: ; Planning solver, we get α =26.027, β =9.074, so GAI=26.027SAI+9.074AAI.

[0026] Theoretically, the above GAI model can predict the activity index of any precursor material, but if the accuracy requirement is extremely high, the steps of the method of the present invention can be used to redefine the GAI model.

[0027] In Table 1, for each precursor material, the activity index calculated by the method of the present invention is compared with its actual activity index to obtain the accuracy. It can be seen from the data that the accuracy of the method of the present invention is very high. At the same time, the optimal proportion of the precursor material can be determined according to the calculated activity index.

[0028] For 9 groups of precursor materials with different ratios consisting of CFBFA, GGBS, and WCP, the above method was used to predict their activity indexes. The specific parameters are shown in Table 2.

[0029] Table 2 Parameters of precursor materials with different ratios of CFBFA, GGBS and WCP ; At the same time, the prediction results of the traditional method and the method of the present invention are compared. Figure 1 It can be seen that the prediction accuracy of the method of the present invention is above 98%.

[0030] In summary, the present invention is not only simple and fast but also has high precision and is suitable for industrial promotion.

[0031] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.

[0032] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A method for predicting the reactivity of a geopolymer precursor material, characterized in that: The following steps are involved: S1: weighing geopolymer precursor material A with different ratios, mixing with NaOH solution and sealing; S2: placing the mixed solution of S1 in a heating device, heating and stirring, and obtaining a composite solution after the reaction is completed; S3: filtering the composite solution; drying and weighing the filter residue obtained by the filtration; S4: Determine the ion concentration in the filtrate obtained by filtration in S3; S5: Calculate the dissolution rate of A using the mass of geopolymer precursor material A in S1 and the mass of filter residue in S3; S6: testing the actual activity index of the geopolymer precursor material A of S1; S7: A calculation formula for obtaining a predicted activity index of geopolymer precursor material A using the dissolution rate of S5 and the ion concentration of S4; S8: Solve the calculation formula of the actual activity index of S6 and the predicted activity index of S7 to obtain a calculation model of the predicted activity index of the precursor material A.

2. A method for predicting the reactivity of geopolymer precursor materials according to claim 1, characterized in that: In S1, The mass of geopolymer precursor material A is M0; the concentration of NaOH solution is 1-3 mol / L; the mass ratio of geopolymer precursor material A to NaOH solution is 1:30-1:

40.

3. A method for predicting the reactivity of geopolymer precursor materials according to claim 1, characterized in that: In S2, The temperature is: 40~65℃; the stirring speed is: 800~2000 r / min; the stirring time is: 40~60min.

4. A method for predicting the reactivity of geopolymer precursor materials according to claim 1, characterized in that: The S3 includes: The composite solution is filtered using a vacuum filtration device, and the filtrate after filtration is stored at a standard curing temperature; the solid filter residue obtained by filtration is washed, dried, and weighed, and the mass is M1.

5. A method for predicting the reactivity of geopolymer precursor materials according to claim 1, characterized in that: The S4 includes: The Si, Al and Ca ion concentrations in the filtrate were determined within 24 h.

6. A method for predicting the reactivity of geopolymer precursor materials according to claim 2 or 4, characterized in that: The S5 includes: The dissolution rate of A The calculation formula is: 。 7. A method for predicting the reactivity of geopolymer precursor materials according to claim 1, characterized in that: The S6 includes: The actual activity index of precursor material A was tested using the intensity ratio method. Precursor material A was mixed with cement to prepare concrete, and its 28-day strength was tested At the same time, pure cement was used to prepare concrete and its 28d strength was tested. , the actual activity index GAI of bulk material A is calculated as follows: 。 8. A method for predicting the reactivity of geopolymer precursor materials according to claim 5 or 7, characterized in that: The S7 includes: Calculate the silicon activation index of precursor material A SAI and aluminum activation index AAI , the calculation formula is: ; in, is the Si ion concentration, is the Ca ion concentration, is the Al ion concentration, is the dissolution rate of precursor material A; Calculate the predicted activity index of precursor material A , the calculation formula is: ; in, and The values ​​are equal, is the activity contribution coefficient of the silicon activation index, is the activity contribution coefficient of aluminum activation index.

9. A method for predicting the reactivity of geopolymer precursor materials according to claim 8, characterized in that: The S8 includes: According to S6 GAI, S7 Calculation formula, obtained through planning solution , , obtain the computational model for the predicted activity index of precursor material A.

Citation Information

Patent Citations

  • Method for predicting active silica-alumina ratio of alkali heat activated geopolymer raw material

    CN114113183A

  • Method for quantitatively analyzing reaction degree of coal ash geopolymer

    CN114460063A

  • Method for predicting geopolymer strength of slag fly ash

    CN117929650A

Cited By

  • Precursor alkali-activated reaction activity prediction method based on physicochemical properties and molecular simulation

    CN119418799A

  • Prediction method of precursor base-induced reaction activity based on physicochemical properties and molecular simulation

    CN119418799B

  • Slag micropowder activity evaluation method based on alkali dissolution method

    CN122193518A

  • A method for evaluating the activity of slag micron powder based on alkali dissolution

    CN122193518B